Advancing Educational Practices: Implementation Of Ebook Based Comics In Islamic Education - Adinda Viola; Faiz Fauzan El Muhammady; Ayu Citra Dewi; Syarifatul Hayati; Rahmat Renaldi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
One of the keys to successful learning is the use of appropriate media that aligns with the diversity of learners, such as media that is easy to understand, engaging, and enjoyable. Therefore, teachers need to be creative and innovative in creating various media as learning aids. This research aims to analyze the effects of using ebook-based comics in the practice of Islamic religious education learning in elementary schools. The research employs the Research and Development method with a 4D type. In the initial stages, the author analyzes the media needs required for learning in elementary schools. Subsequently, the author designs the product, starting from narrating the story, creating sketches, Line Art, Coloring, and Texting the story that will be made into an ebook. After the product was designed, a feasibility test was conducted with two experts related to learning media and Islamic education materials. Finally, after the experts finished evaluating the product, the author implemented the completed product into the learning practice at the elementary school. As a product feasibility test, the author collected data from teachers using a questionnaire, while for students, the author conducted direct observations to see whether the created product could operate well and have an impact on learning. All data were analyzed using SPSS 22 software with descriptive analysis techniques. The research results show that the designed and produced product received good ratings from both experts after going through several stages of improvement, even reaching scores of 80-90. Meanwhile, regarding the effect of the produced product on learning, it has proven to be positively impactful on the students, meaning this media is suitable to be used as one of the learning tools.